2020
DOI: 10.1186/s43055-020-00192-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the outcome of single versus multiple uterine fibroids after uterine artery embolization

Abstract: Background: Uterine fibroids are the most common benign tumor of the reproductive tract in women. Uterine artery embolization has been approved as an alternative treatment option for uterine fibroids to reduce uterine and fibroid volumes as well as to relieve the patient symptoms. The current study included 80 patients with symptomatic uterine fibroids. All patients underwent pre-embolization MRI, uterine artery embolization, and followup post-embolization MRI at 6 months post procedure for a reduction in uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In elaboration, according to Lipscomb, et al [39] ibroids larger than 8.7 cm showed lesser reduction in size where stated each centimeter increase in ibroid size there was a corresponding 10% increase in failure rate. Having multiple ibroids per se is another cause, as El-Sharkawy, et al [40] observed a signi icant reduction in single rather than multiple ibroids.…”
Section: Discussionmentioning
confidence: 99%
“…In elaboration, according to Lipscomb, et al [39] ibroids larger than 8.7 cm showed lesser reduction in size where stated each centimeter increase in ibroid size there was a corresponding 10% increase in failure rate. Having multiple ibroids per se is another cause, as El-Sharkawy, et al [40] observed a signi icant reduction in single rather than multiple ibroids.…”
Section: Discussionmentioning
confidence: 99%